Must an individual union member’s rights be sacrificed to protect the group interest? - Bromstein, Reuben (Relations industrielles / Industrial Relations, 1970)
Assuming that an individual employee can neither sue directly on the collective agreement nor force the union to take his case through to arbitration, can he proceed against the union for its failure to discharge its duty to represent his interests?